Анексія Криму: інформаційний супровід - Тихомирова, Євгенія Борисівна; Tykhomyrova, Yevheniia B. (Київський національний університет імені Тараса Шевченка, 2019)
У статті розкривається проблема інформаційної підготовки та інформаційного супроводу анексії Криму. Констатується, що оку¬пація Криму стала наслідком реалізації російською владою дов¬готривалої стратегії, що базувалася на специфічному імперсько¬му баченні Росією свого місця в регіоні та світі. Оскільки підготовка до агресії проти України здійснювалася цілеспрямовано та послідовно задовго до 2014 р., проведено аналіз інформаційних операцій, реалізованих російськими засобами масової комунікації до початку (період латентної фази підготовки анексії Криму) та після здійснення анексії Криму. Розкрито зміст основних апологетичних наративів, які сприяли введенню у масову свідомість різних цільових аудиторій проблематики анексії Криму: анексія Криму має історичне підґрунтя та її майже одноголосно підтримує все населення півострова.

The article reveals the problem of information preparation and informational support of the annexation of the Crimea. It is noted that the Crimean occupation was the result of the Russian government's implementation of a long-term strategy, based on the specific imperial vision of Russia for its place in the region and the world. As preparations for aggression against Ukraine were carried out purposefully and consistently long before 2014, an analysis of information operations implemented by Russian mass media before the beginning (during the latent phase of the Crimean annexation preparation) and after the annexation of the Crimea was carried out. The content of the main apologetic narratives has been clarified, which contributed to the introduction of Crimea annexation issues into the mass consciousness of various target audiences: the Crimean annexation has a historical background and almost unanimously supports the entire population of the peninsula.
Annexation of Crimea: information support
Keywords: анексія Криму; інформаційний вплив; інформаційна операція; інформаційний супровід; annexation of Crimea; informational influence; informational operation; information support